Î²-Carotene in mango (Mangifera indica L.). - Sulbarán, Betzabé; Manríquez, Elba; Ojeda de Rodríguez, Graciela; Nava, Rosa; Berradre, María; Fernández, Viluzca; Peña, Jorge (Multiciencias)
Ver resumen pdf.